The Influence of Organizational Culture, Work Motivation and Work Discipline on Employee Performance at the Maluku Provincial Transportation Service - Tomasouw, Katherina Florencia; Lewaherilla, Novalien Carolina; Leuhery, Ferdy (SEAN Institute, 2024)
This study aims to determine the effect of organizational culture, work motivation and work discipline on employee performance at the Maluku Provincial Transportation Office. The method used in this study is a quantitative method involving all civil servants (PNS) of the Maluku Province Transportation Service, totaling 62 people as a population. The sample in this study amounted to 54 employees. The sampling technique used in this research is stratified random sampling. The measurement tool used is SPSS version 26. The results of the study show thatOrganizational culture partially has a significant effect on employee performance at the Maluku Province Transportation Service, as evidenced by the tcount = 2.377 greater than the ttable = 1.675, work motivation partially has a significant effect on employee performance at the Maluku Province Transportation Service, evidenced by the tcount = 2.158 greater than the value of ttable = 1.675 and work discipline partially has a significant effect on employee performance at the Maluku Provincial Transportation Office,evidenced by the value of tcount = 2,964 greater than the value of ttable = 1,675. The better the application of organizational culture, the better the performance of employees, as well as if the higher the motivation and work discipline, the higher the performance of employees. Conversely, the lower the application of organizational culture, work motivation and work discipline, the lower the employee performance. This means that the research hypothesis can be accepted.